Inositol trisphosphate 3-kinase B is increased in human Alzheimer brain and exacerbates mouse Alzheimer pathology. (8th January 2014) - Stygelbout, Virginie; Leroy, Karelle; Pouillon, Valérie; Ando, Kunie; D'Amico, Eva; Jia, Yonghui; Luo, H. Robert; Duyckaerts, Charles; Erneux, Christophe; Schurmans, Stéphane; Brion, Jean-Pierre
Abstract : Inositol (1, 4, 5) trisphosphate 3-kinase B (ITPKB) is increased in Alzheimer's disease brain tissue. Stygelbout et al . report an increase in dystrophic neurites near amyloid plaques. In vitro or in vivo ITPKB overexpression exacerbates Alzheimer pathology in a mouse model, via a pathway involving extracellular signal-regulated kinases and β-secretase 1. Abstract : ITPKB phosphorylates inositol 1, 4, 5-trisphosphate into inositol 1, 3, 4, 5-tetrakisphosphate and controls signal transduction in various hematopoietic cells. Surprisingly, it has been reported that the ITPKB messenger RNA level is significantly increased in the cerebral cortex of patients with Alzheimer's disease, compared with control subjects. As extracellular signal-regulated kinases 1/2 activation is increased in the Alzheimer brain and as ITPKB is a regulator of extracellular signal-regulated kinases 1/2 activation in some hematopoietic cells, we tested whether this increased activation in Alzheimer's disease might be related to an increased activity of ITPKB. We show here that ITPKB protein level was increased 3-fold in the cerebral cortex of most patients with Alzheimer's disease compared with control subjects, and accumulated in dystrophic neurites associated to amyloid plaques. In mouse Neuro-2a neuroblastoma cells, Itpkb overexpression was associated with increased cell apoptosis and increased β-secretase 1 activity leading to overproduction of amyloid-β peptides. In this cellular model, an inhibitor of mitogen-activated kinase kinases 1/2 completely prevented overproduction of amyloid-β peptides. Transgenic overexpression of ITPKB in mouse forebrain neurons was not sufficient to induce amyloid plaque formation or tau hyperphosphorylation. However, in the 5X familial Alzheimer's disease mouse model, neuronal ITPKB overexpression significantly increased extracellular signal-regulated kinases 1/2 activation and β-secretase 1 activity, resulting in exacerbated Alzheimer's disease pathology as shown by increased astrogliosis, amyloid-β40 peptide production and tau hyperphosphorylation. No impact on pathology was observed in the 5X familial Alzheimer's disease mouse model when a catalytically inactive ITPKB protein was overexpressed. Together, our results point to the ITPKB/inositol 1, 3, 4, 5-tetrakisphosphate/extracellular signal-regulated kinases 1/2 signalling pathway as an important regulator of neuronal cell apoptosis, APP processing and tau phosphorylation in Alzheimer's disease, and suggest that ITPKB could represent a new target for reducing pathology in human patients with Alzheimer's disease with ITPKB expression.